Securitizing Rohingya refugees: Domestic opinion, media narratives, and Indonesia’s foreign policy (2015–2023) - Lutfiarifulloh; Agustina Rahmawati (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2026)
This article examines why and how Indonesia’s approach to Rohingya refugees shifted from humanitarian solidarity to a more securitized and burden‑oriented stance between 2015 and 2023. Drawing on securitization theory, it employs a qualitative case study based on document analysis of Indonesian legal and policy instruments, official statements, ASEAN records, reports from international organizations, media coverage, and academic studies. The analysis identifies three interrelated dynamics. First, public attitudes in key host areas, especially Aceh, have moved from empathy to resentment as prolonged refugee presence, economic pressures, and distributive grievances increasingly frame Rohingya as social and economic burdens, creating receptive audiences for restrictive policies. Second, media narratives have progressively foregrounded themes of disorder, illegality, and links to irregular migration, which normalize security‑oriented interpretations of refugee arrivals and legitimize calls for tighter control. Third, a legal–institutional framework that treats refugees as temporary foreign guests, combined with ASEAN’s limited burden‑sharing and strong non‑interference norm, enables the state to recalibrate between humanitarian and security logics while maintaining a humanitarian diplomatic posture. By tracing these dynamics across key turning points from 2015 to 2023, the article refines the application of securitization theory to refugee‑hosting states in the Global South and shows how domestic opinion, media framings, and regional constraints jointly shape the space of possible foreign policy responses toward the Rohingya.